Synthesis and hetero-Diels–Alder reactions of enantiomerically pure dihydro-1H-azepines. Issue 68 (24th July 2020) - Craig, Donald; Spreadbury, Samuel R. J.; White, Andrew J. P.
Abstract : Thermolysis of enantiomerically pure 3-substituted 7, 7-dihalo-2-azabicyclo[4.1.0]heptanes in the presence of K2 CO3 gives in good yields 2-alkyl-6-halo-1-tosyl-2, 3-dihydro-1 H -azepines. Abstract : Thermolysis of enantiomerically pure 3-substituted 7, 7-dihalo-2-azabicyclo[4.1.0]heptanes in the presence of K2 CO3 gives in good yields 2-alkyl-6-halo-1-tosyl-2, 3-dihydro-1 H -azepines. These undergo highly stereoselective [4+2] cycloaddition reactions with heterodienophiles and arylation/alkenylation under Suzuki conditions.